THE GENESIS OF ACTOR’S DEVELOPMENT IN AUDIOVISUAL ART - Lychkovska , Nataliia (Global Prosperity, 2022)
This article analyzes the main stages of the formation of acting in audiovisual art in the context of the genesis of a new art form in Ukraine. An analytical interpretation of these stages has been carried out, the research focus is on the period from the beginning of the 20th century to the 1920s inclusive. In particular, the characterization of the artistic features of the development of the acting art period at the end of the 19th century in Kharkov, as well as at the beginning of the 20th century in Odessa and other cities is presented. Considerable attention is paid to the peculiarities of the development of acting in audiovisual art during the Ukrainian national liberation revolution of 1917-1920, when acting in Ukrainian cinema was carried out in extreme geopolitical conditions, in particular, within the framework of the functioning of the film production company Ukrainfilm. Cardinal artistic changes during the period of the seizure of Ukrainian territories by the Bolshevik authorities were due to the ideologization of cinematography in the context of Bolshevik ideological trends. In conclusion, the features of the stylistic formations of the period under study are stated. It was established that the crisis phenomena (wars, revolutions and social conflicts) characteristic of the beginning of the 20th century contributed to the creation of a depressed state of society in the territories of Western and Eastern Europe and determined the conditions for the creation of a new direction of artistic development - modernism. In the interwar period, Ukrainian theater and cinema at the beginning of the 20th century acquired new features and aspects of interaction: a new subjective approach of the actor to the creative process was formed, during the acting game based on established traditions, innovative trends arose in the methods of combining various components of time and space within a single screen reality.